Pengaruh kualitas produk dan kualitas layanan terhadap keputusan pembelian sepeda motor honda - Amrullah, Amrullah; Siburian, Pamasang S; Zainurossalamia, Saida (Faculty of Economics and Business Mulawarman University, 2016)
This research aims to determine whether the product Quality positive and significant impact on the purchase decision and whether Quality of Service positive and significant impact on the purchase decision. The independent variables in this study is the Product Quality and Service Quality . While the dependent variable is the purchase decision . This research was conducted at Honda Star Motor Dealers Samarinda , using a sample of 60 consumers who meet the criteria . This research is quantitative . The data collection is done by collecting a questionnaire to test the Product Quality and Service Quality partially. Data were analyzed using multiple linear regression . The results of this study indicate that the product quality is positive and significant impact on the purchase decision and Quality of Service positive and significant impact on the purchase decisionKeywords: Product Quality, Service Quality, Purchase Decision